Edukasi Pembuatan dan Penyemprotan Desinfektan pada Masyarakat di Desa Bukek Kecamatan Tlanakan Kabupaten Pamekasan - Hasan Basri; Sri Indriati Hasanah; M. Khoiri Khoiri (Jurnal SOLMA, 2021)
Background: Indonesia was one of the countries hardest hit by the Covid pandemic. Low-income families in Bukek Village, Tlanakan Sub-District cannot afford to buy disinfectant. Provide an understanding of the importance of preventing the transmission of Covid-19 and provide skills to make disinfectants using materials commonly used in households, such as floor cleaners, clothes bleach and water. Method: The implementation method goes through three stages, namely the preparation stage, the implementation stage and the observation stage. The preparation stage includes observation, and coordination with the village. The implementation stage includes socialization activities and spraying of disinfectants, while the evaluation stage is carried out through the provision of questionnaires. Result: The community knows the ingredients used to make disinfectant liquid. The community is also able to make disinfectants independently. As well as several points or crowded locations spraying disinfectant has been carried out. Conclusion: The socialization activities and the spraying of disinfectants went very smoothly because of the support from both the village apparatus and the surrounding community. The impact of the implementation of the activities is also very felt for the community, this can be seen from the results of the questionnaire which showed a positive response from the respondents' answers.